FDA’s approval of resmetirom (Rezdiffra): a breakthrough in MASH management - Muhammad Mazhar Azam; Sameen Mukhtar; Muhammad Haris; Fatima Laique; Suhaina Amir; Mubashir Mohiuddin; Bibek Giri (Exploration of Drug Science)
The FDA’s approval of resmetirom (Rezdiffra) marks a significant breakthrough in treating metabolic dysfunction-associated steatohepatitis (MASH) and fibrosis, conditions linked to non-alcoholic fatty liver disease (NAFLD). MASH is a growing global health concern, and resmetirom offers a novel therapeutic option by targeting liver pathophysiology through thyroid hormone receptor-beta activation. This mechanism effectively reduces fibrosis markers, improves liver enzyme levels, and minimizes liver fat buildup. Clinical trials have shown that resmetirom has a favorable safety profile, with manageable side effects like diarrhea and nausea. Additionally, it may lower cardiovascular risks associated with MASH, enhancing patient outcomes and quality of life. As the first FDA-approved drug for MASH, resmetirom’s introduction fills a crucial treatment gap, providing new hope for millions of patients and representing a pivotal moment in hepatology.